Kebijakan Pendidikan Tentang Pelaksanaan Merdeka Belajar - Muhammad Iqbal; Alfiq Rizki; Julia Sapira Wardani; Nanda Putri Khafifah; Nurhasanah Silitonga; Ridha Amirah (Journal on Education, 2023)
Merdeka Learning is a new policy given by the government to promote quality education. Quality education is education that is able to carry out the process of maturing the quality of students which is developed by freeing students from ignorance and incompetence. With quality education, generations or superior human resources will be born in all aspects of life. Many policies have been carried out by the government to improve the quality of education, such as the independent learning policy. Educational institutions are no less lagging behind in improving the quality of education by continuing to improve the quality of human resources and the quality of learning. The method used in this study is a qualitative method with a descriptive analysis approach, where descriptive research in this case is research that aims to describe the independent learning policy as an effort to improve the quality of education.